THE TRADITION OF SIAT SAMPIAN IN BEDULU VILLAGE - Utami, Ni Komang Putri; Widhiantari, Ni Kadek Menuh; Permanamiarta, Putu Agus (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2023)
The function and meaning as well as the aesthetic value of the siat sampian tradition are made to inform and present Bali with beautiful nature wrapped in local wisdom as well as various unique traditions on the island of the gods which are inherited from ancestors that still survive to this day. As one of them is known as siat sampian. Siat sampian is a unique tradition that is routinely held at Samuan Tiga Temple, Bedulu village, Blahbatuh District, Gianyar Regency. This tradition is held during a series of pujawali or piodalan ceremonies at Samuan Tiga Temple in Bedulu and is located in the central jaba area of the temple. Sampian is the symbol of Lord Vishnu's weapon. The assumption of the community, especially in the local area, is that they believe that this ritual is an abstract treatment medium, since decades, this belief has been used as a way of life by the community. This tradition can only be followed by people who have mewinten or people who have been entrusted with being Jero or Pemangku.